Implementasi Kebijakan Pemberdayaan Masyarakat Pesisir dalam Mendukung Pertahanan Maritim Indonesia (Studi Peraturan Daerah Kota Surabaya Nomor 10 Tahun 2016 Tentang Rencana Pembangunan Jangka Menegah Daerah Kota Surabaya Tahun 2016-2021) - Rudiawan, Beni; Sumartono, Sumartono; Mardiyono, Mardiyono; Saleh, Choirul (Jurnal Ilmiah Administrasi Publik, 2021)
This study aims to analyzes the empowerment of coastal communities in Surabaya as planned by the Surabaya City Government (Pemkot) in the Regional Regulators (Perda) Number 10 of 2016 concerning on Medium-Term Development Region Plans (RJPMB) of Surabaya City year 2016-2021. Data were collected by descriptive analysis research methods and approaches qualitative. The data were validated by interviews, observations, and documentations that shows the implementation of coastal community empowerment policies who was done by the Surabaya City Government to support Indonesia’s maritime defense that has not been done. Based on Grindle’s policy implementation theory approach and the empowerment model community by Hyman, the study revealed that coastal communities can be empowered to become one of the elements of Indonesia’s maritime defense force and the deterrent againts the threats of the transnational crimes that use marine and coastal areas as an alternative media.